Presentation and management outcome of childhood intussusception in Lagos: A prospective study - Bode C (Wolters Kluwer Medknow Publications, 2008)
Background: Intussusception is the commonest cause of bowel obstruction in infancy and childhood. Early diagnosis and effective management have reduced its morbidity and mortality in developed countries. Aim: To document the presentation, management and treatment outcome of intussusceptions at the Lagos University Teaching Hospital (LUTH). Patients and Methods: One hundred seventy-four consecutive cases of this condition seen in children presenting at LUTH over a 5-year period were prospectively studied. Details of symptoms and signs, pre-hospital care, treatment, and outcome in LUTH were documented. Results: The triad of abdominal pain, bloody mucoid stools and palpable abdominal mass was seen in 106 (61%) of the cases. One hundred thirty-five (77.6%) had been admitted and treated with antibiotics and intravenous fluids in primary healthcare centers for an average of 3 days before referral to the LUTH. Prolonged mean duration of recognizable symptoms of 3 days accounted for a 70.4% bowel resection rate. Wound infection occurred in 61 (36.1%), whereas fecal fistulae developed in six (3.6%), and burst abdomen in five (3%) of cases. Seven (4.1%) patients developed incisional herniae. Overall, mortality rate was 12.1%. Conclusion: The early symptoms of intussusception would seem to be missed by primary healthcare workers in Lagos, with consequently high morbidity and mortality. There is an urgent need to re-emphasize these symptoms to first-line healthcare providers and parents through public enlightenment campaigns.